Pengaruh Literasi Keuangan dan Financial Technology Terhadap Inklusi Keuangan Masyarakat Desa Beraban, Kecamatan Kediri. - Ni Putu Shita Dewi Maharani; Surya Dewi Rustariyuni (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The national financial literacy index in 2025 is recorded at 66.64 percent, while the financial inclusion index reaches 92.74 percent, indicating a gap between the public’s level of understanding and the use of financial products. This study aims to analyze the influence of financial literacy and financial technology on the financial inclusion of the Beraban Village community. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 100 respondents and analyzed using descriptive statistical analysis and multiple linear regression analysis. The results show that financial literacy and financial technology have a significant effect on financial inclusion, both simultaneously and partially. These findings are expected to serve as a basis for the development of the digital village concept in other areas so that the utilization of financial technology and improvements in financial literacy can support the enhancement of financial inclusion in local communities.